2022
DOI: 10.1140/epjc/s10052-022-10670-w
|View full text |Cite
|
Sign up to set email alerts
|

Virtual neutrino propagation at short baselines

Abstract: Within a covariant perturbative field-theoretical approach, the wave-packet modified neutrino propagator is expressed as an asymptotic expansion in powers of dimensionless Lorentz- and rotation-invariant variables. The expansion is valid at high energies and short but macroscopic space-time distances between the vertices of the proper Feynman macrodiagram. In terms of duality between the propagator and the effective neutrino wave packet, at short times and distances, neutrinos are deeply virtual and move quasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…With this at hand and properly normalizing the initial and final states (25) we derived the flavor conversion Master Formula for differential rate of the process (8) valid under the approximation m m E i k 2 2  n . For the particular process (33) we demonstrated that the presented approach leads to a probability formula for ν μ → ν e neutrino oscillation corrected with respect to the conventional one by terms ∼m k /E ν , which can be large for heavy neutrino quasi degenerate states.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…With this at hand and properly normalizing the initial and final states (25) we derived the flavor conversion Master Formula for differential rate of the process (8) valid under the approximation m m E i k 2 2  n . For the particular process (33) we demonstrated that the presented approach leads to a probability formula for ν μ → ν e neutrino oscillation corrected with respect to the conventional one by terms ∼m k /E ν , which can be large for heavy neutrino quasi degenerate states.…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, this happens under certain reasonable approximations, so that in the rest frame of the target neutron we arrive at G p + in (35). They both give the rate of the same process (33), while the conventional approach (35) assumes factorization of the process (33) in the three separate steps (34). We find that both results coincide in structure if we interpret as the QFT oscillation probability the expression…”
Section: Application Of the Master Formula For Process Involving Osci...mentioning
confidence: 85%
See 2 more Smart Citations